2021
DOI: 10.1093/cid/ciab714
|View full text |Cite
|
Sign up to set email alerts
|

Post-Vaccination Coronavirus Disease 2019: A Case-Control Study and Genomic Analysis of 119 Breakthrough Infections in Partially Vaccinated Individuals

Abstract: Background Post-vaccination infections challenge the control of the COVID-19 pandemic. Methods We matched 119 cases of post-vaccination SARS-CoV-2 infection with BNT162b2 mRNA, or ChAdOx1 nCOV-19, to 476 unvaccinated patients with COVID-19 (Sept 2020-March 2021), according to age and sex. Differences in 60-day all-cause mortality, hospital admission, and hospital length of stay were evaluated. Phylogenetic, single nucleotide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
1
12
0
2
Order By: Relevance
“…This implies that COVID-19 vaccine acceptance and uptake among young adults is related to the perceived severity of COVID-19 rather than the perceived chance of getting it. One reason for this might be that while COVID-19 vaccination reduces the severity of symptoms and number of deaths [49], it does not automatically prevent infection because immunity may wane over time [50]. Incidence of COVID-19 among young adults is high, while the burden of disease is relatively low [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that COVID-19 vaccine acceptance and uptake among young adults is related to the perceived severity of COVID-19 rather than the perceived chance of getting it. One reason for this might be that while COVID-19 vaccination reduces the severity of symptoms and number of deaths [49], it does not automatically prevent infection because immunity may wane over time [50]. Incidence of COVID-19 among young adults is high, while the burden of disease is relatively low [51].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, while the mortality of young adults with COVID-19 is low [51], more and more cases in which young adults suffer from severe and long-term symptoms are found [53]. Vaccination will help to lower the severity of the symptoms and decrease mortality [49].…”
Section: Practical Implicationsmentioning
confidence: 99%
“…The differences with our results may be due to different patterns of variants circulation, as, for example, circulation of Beta VOC was very tiny in our territory. According to other studies, the analysis of the Spike mutations in each lineage, broken down by Groups 1, 2, and 3, indicated that there is no selection for the enrichment of any particular mutation in fully vaccinated individuals (Group 3) as compared to individuals with incomplete vaccination (Groups 1 and 2) ( 36 ).…”
Section: Discussionmentioning
confidence: 95%
“…It has been suggested that vaccination may result in a reduced length of stay [25], though evidence in this regard is limited. The reduced length of stay observed between the two epidemic periods could be a result of the changes in vaccination coverage.…”
Section: Discussionmentioning
confidence: 99%